HOW PRODUCT REVIEWS AND ADVERTISING AFFECT PURCHASING DECISIONS OF GENERATION Z IN BANDUNG CITY - Makarim, Rafie; Prio Pratomo, Triaji (The International Journal of Business Review (The Jobs Review), 2023)
The increase in the number of internet users  in the city of Bandung by 82.5%  with the number of   users 2.1 million people, especially Generation Z who are very familiar with the  use of digital  technology such as the internet. This provides potential for the  Marketplace which has an impact on competitiveness in  the  E-commerce  business industry in marketing activities.  This research was conducted to determine the  influence of product reviews and advertisements on purchasing decisions  by Generation Z in the city of Bandung at the  Shopee Marketplace.   This study used the kuantitative method with a descriptive type of research.  Sampling was   carried out using a non-probabilty  sampling method and  the number of respondents was 200 Generation Z people in the city of Bandung.  The  data  analysis technique used is linear  regression analysis. The results showed that the  product review variable obtained results of 75.7% and was included in the good category, the advertising variable obtained results of  73.8% and   was included in the good category, and the purchase decision variable obtained results of  77.1% and falls into the good category. Based on the results of hypothesis testing, it resulted that product reviews and advertisements had a positive and significant influence on purchasing decisions by Generation Z in the city of Bandung at the Shopee Marketplace.